Computational physics - Thijssen, J. M. (Joseph Marie), 1958- (Cambridge University Press, 2007)
This edition has been fully updated with several new sections and chapters. It covers many different areas of physics research and different computational methodologies. Throughout the book the relations between the methods used in different fields of physics are emphasised.